IMPLEMENTASI ALGORITMA SUBEXPONENTIAL CODE UNTUK KOMPRESI FILE GAMBAR - Amir Maniur Silitonga; Surya Darma Nasution; Putri Ramadhani (STMIK Budi Darma, 2019)
Image file size is sometimes relatively large where the better the quality of the image produced, the pixel shape needed to record the image is bigger. With a very large image file size, at the time of the transfer process the transfer process could fail because the storage space media exceeds its limit. As for the Solution in this problem is how the image file can be compressed in order to accelerate the transfer and storage of image files. compression on image files is done by reducing the shape of the image file by reducing the bit in the image file, but does not eliminate the information data in it. By running compression, large files will shrink in size so that it can save storage space. In this study, the algorithm used is Subexponential Code, by using this method, the compression results from the k value have different results from each value, and the compression results will be advantageous in sending, and transferring image files will be easier.Keywords: image file compression, subexponential code algorithm